2006
DOI: 10.2174/138161206778194042
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Hypersensitivity Reactions to Penicillins and Other Betalactams

Abstract: Immediate hypersensitivity reactions to betalactams are IgE mediated and constitute the most frequent allergic reactions mediated by specific immunological mechanisms. IgE responses to benzyl penicillin (BP), the first antibiotic producing the benzyl penicilloyl structure (BPO), are characterized by a quick release of inflammatory mediators, resulting in anaphylactic shock, urticaria and angioedema. With the progressive appearance of other structures, comprising cephalosporins, carbapenems, monobactams and cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 60 publications
(107 reference statements)
0
39
0
Order By: Relevance
“…In recent years, a number of studies have supported this finding [2][3][4][5]. In contrast to reactions to ß-lactams (BLs), which are immunologically mediated [6], DHRs to NSAIDs may be induced by both specific immunological mechanisms (allergic or selective reactions [SRs]) and mechanisms not based on immunological recognition (cross-hypersensitivity reactions [CRs]) [7]. Although the latter are responsible for the largest number of affected patients in some countries [1,8], SRs account for a considerable proportion in others [9,10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of studies have supported this finding [2][3][4][5]. In contrast to reactions to ß-lactams (BLs), which are immunologically mediated [6], DHRs to NSAIDs may be induced by both specific immunological mechanisms (allergic or selective reactions [SRs]) and mechanisms not based on immunological recognition (cross-hypersensitivity reactions [CRs]) [7]. Although the latter are responsible for the largest number of affected patients in some countries [1,8], SRs account for a considerable proportion in others [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence indicating that individuals may react to several NSAIDs but tolerate ASA [10,26]. Contrary to BL reactions, where all drugs share a common ring that may influence the specificity of the response and cross-reactivity [6,18], NSAIDs comprise a heterogeneous family of chemical structures with a variable degree of cross-reactivity within each group [9,11]. In this manuscript, we present findings for a series of patients who developed immediate SRs to 2 or more NSAIDs, verify tolerance to ASA, and assess the involvement of the culprit drug(s) using challenge testing.…”
Section: Introductionmentioning
confidence: 99%
“…Nonsteroidal anti-inflammatory drugs (NSAIDs) are the most frequent medicines involved in drug hypersensitivity reactions in both adults [2] and children [3] followed by β-lactam antibiotics [4]. Hypersensitivity reactions to NSAIDs have been classified into different categories depending on the clinical symptoms induced, the number of NSAIDs involved and the presence or absence of underlying disease [5].…”
Section: Introductionmentioning
confidence: 99%
“…Hypersensitivity reactions to β-lactam antibiotics are among the most common drug reactions [1,2,3]. Since their introduction to the market, penicillin skin tests with major (benzylpenicilloyl-polylysine, PPL) and minor determinants (minor determinant mixture, MDM) of penicillin have had a major impact on the diagnosis of immediate hypersensitivity to β-lactams [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Since their introduction to the market, penicillin skin tests with major (benzylpenicilloyl-polylysine, PPL) and minor determinants (minor determinant mixture, MDM) of penicillin have had a major impact on the diagnosis of immediate hypersensitivity to β-lactams [1,2]. Application of these tests in clinical practice has revealed that the majority of patients with a history of immediate reactions to β-lactams were not really allergic to penicillin [4,5].…”
Section: Introductionmentioning
confidence: 99%